Qualidade de vida de pessoas com doença renal crônica em hemodiálise - Christielle Lidianne Alencar Marinho; Jeany Freire de Oliveira; Jéssica Eidler da Silva Borges; Rudval Souza da Silva; Flávia Emília Cavalcante Valença Fernandes (Universidade Federal do Ceará, 2017)
Objective: to analyze the quality of life of people with chronic kidney disease. Methods: cross-sectional, descriptive study with people undergoing hemodialysis. Data collection was performed with 105 participants. The Kidney Disease and Quality-of-Life Short-Form was used. Data were analyzed using mean, median and standard deviation. Results: the sample was predominantly male, older than 60 years and did not work. Work Status and Physical Function were the most affected quality of life dimensions, with averages of 14.76 and 43.1, respectively. The Cognitive Function and the Sexual Function presented the best results, with averages of 86.41 and 86.56. Conclusion: chronic kidney disease and hemodialysis treatment interfere with the individuals' quality of life, bringing greater losses in the work status and physical function, and better repercussion in the domains pain, social function, cognitive function and sexual function.